Boundary Work, Interloper Media, And Analytics In Newsrooms: An analysis of the roles of web analytics companies in news production. Issue 4 (21st April 2018) - Belair-Gagnon, Valerie; Holton, Avery E.
Abstract : Amid the increasing use of web analytics to gage the success, present and future, of news content and related news products, this article focuses on in-depth interviews with the suppliers of those analytics: web analytics companies. Drawing on the concepts of boundary work and interloper media, this article examines how managers for these companies understand and position their work in relation to news production as a boundary object. The larger finding of this article is that while web analytics companies seek to understand and address news production values and norms without assuming responsibility as journalists, they foster profit-oriented norms and values in newsrooms by introducing web analytics as disruptive, connective, and routinized in news production. By offering a product that they (i.e. web analytics companies) need to modify on a continuous basis because of changes in the structure of the web and audience behaviors, they foster a milieu of constant experimentation with old and new products. This and other findings provide a portrait of the development of norms and values in journalism as these companies gain a greater acceptance in newsrooms and increasingly influence news production.